Detection of Testicular Metastasis from Renal Cell Carcinoma on PSMA-PET Scan (Journal of Kidney Cancer, 2024)
The use of prostate-specific membrane antigen–positron emission tomography (PSMA-PET) is becoming more widespread for the diagnosis and management of prostate cancer. Here we report a case of oligometastatic renal cell carcinoma (RCC) to the testes diagnosed incidentally on PSMA-PET imaging. This case demonstrates the potential for diagnosis of nonprostate disease with PSMA-PET imaging, as well as the promising nature of PSMA-PET for the diagnosis and surveillance of RCC. In addition, this case report discusses the rare occurrence of oligometastatic RCC to the testis.